A disconnect between upslope shifts and climate change in an Afrotropical bird community. Issue 11 (6th October 2020) - Neate‐Clegg, Montague H. C.; O'Brien, Timothy G.; Mulindahabi, Felix; Şekercioğlu, Çağan Hakkı
Abstract: Climate change threatens to push species to higher elevations and eventual extinction. Birds, in particular, are shown to be shifting upslope in the Neotropics and Southeast Asia. Yet previous studies have lacked the temporal resolution to investigate distributional dynamics over time in relation to climatic fluctuations, especially in the understudied Afrotropics. Here, we used 15 years of point‐count data from across an elevational gradient (1, 767–2, 940 m) in Rwanda, to assess elevational shift rates and dynamics in a community of Afrotropical birds. In general, species shifted their elevations upslope by 1.9 m/year, especially at their lower elevational limits which shifted by 4.4 m/year. Importantly, these shifts occurred despite the fact that local temperature and precipitation showed little trend over the study period. Moreover, the interannual distributions of few species were associated with temperature, suggesting that temperature played little direct role in determining elevational distributions of birds. Instead, upslope shifts may be more related to incremental shifts in habitat and resources which lag behind decades of increased temperature in the region. Precipitation appeared to have more of an effect than temperature in determining interannual elevational changes, allowing species to expand their ranges in years of higher rainfall. Our results highlight the need to understand the mechanisms driving upslope shifts as they occur throughout the tropics. It will be critical for montane regions of the tropics to preserve contiguous blocks of forest across elevational gradients to allow wildlife to shift unimpeded. Abstract : Across 15 years of bird count data in Nyungwe National Park, Rwanda, we show that species have shifted their elevations upslope. However, these shifts did not coincide with increases in temperature. There was little association between temperature fluctuations and bird distributions but birds appeared to expand their distributions in wetter years.